Phase-error-measurement and compensation in PLL frequency- synthesizers for FMCW sensors - I: Context and Application - Pichler, Markus; Stelzer, Andreas; Gulden, Peter; Seisenberger, Claus; Vossiek, Martin (IEEE Transactions on Circuits and Systems I-Regular Papers, 2007)
The synthesis of linear frequency sweeps or chirps is required, among others, in frequency-modulated continuous-wave radar systems for object position estimation. Low phase and frequency errors in sweeps with high bandwidth are a prerequisite for good accuracy and resolution, but, in certain applications where high measurement rates are desired, the additional demand for short sweep cycles has to be met. Transient phenomena in dynamic synthesizers as well as nonlinear system behavior usually cause unknown phase errors in the system output. For the class of phase-locked-loop (PLL)-based frequency synthesizers, a novel output phase-measurement method and dedicated circuitry are proposed that allow significant reduction of phase errors by adaptive input predistortion. The measurement procedure is implemented within the PLL control circuitry and does not require external equipment. The application of this method to PLL system identification and linearization of extremely short frequency sweeps is shown. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.phasee
Keywords: Chirp radar; Frequency synthesizers; Phase measurement; Phase-locked loops (PLLs)